2015
DOI: 10.1093/icvts/ivv022
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for postoperative recurrence of spontaneous pneumothorax treated by video-assisted thoracoscopic surgery

Abstract: VATS blebectomy and parietal pleurectomy is a safe procedure for treatment of spontaneous pneumothorax in young patients, with a 6% long-term recurrence rate in our experience. Postoperative recurrence significantly correlates with female gender and with prolonged air leakage after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 25 publications
2
30
1
1
Order By: Relevance
“…Previous studies have reported that female sex, young age, smoking habit, presence of bilateral PSP, the area of RAS, the size and distribution of bullae, and incomplete bullectomy are risk factors for postoperative recurrence of PSP. 8,10,12,18,19) However, few previous studies have reported the impact of a change in the alveolar structure at the base of blebs and bullae on the recurrence of PSP after VATS bullectomy. Histological analysis of resected blebs and bullae is usually performed to identify unexpected lung diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that female sex, young age, smoking habit, presence of bilateral PSP, the area of RAS, the size and distribution of bullae, and incomplete bullectomy are risk factors for postoperative recurrence of PSP. 8,10,12,18,19) However, few previous studies have reported the impact of a change in the alveolar structure at the base of blebs and bullae on the recurrence of PSP after VATS bullectomy. Histological analysis of resected blebs and bullae is usually performed to identify unexpected lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“…2,4) Structural changes in the lung parenchyma are involved in the pathogenesis of PSP. 1,8) However, their relationship with the recurrence of PSP after VATS bullectomy has not been evaluated because PSP occurs without any apparent underlying lung disease. 8) After blebs and bullae occur from the degradation of elastic fibres, an increase in alveolar pressure due to small airway obstructions ruptures them, resulting in spontaneous pneumothorax.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many authors supporting that observation, aspiration and tube thoracostomy would be enough in the first attack in the treatment of primary spontaneous pneumothorax. While recurrence rate after the first attack is indicated as 23-50% in those treated with non-surgical methods, the probability of recurrence after 2 and more attacks rises to 60-80% 1,2 . The majority of surgeons prefer blebectomy/bullectomy and parietal pleurectomy or abrasion procedures in order to prevent recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now input methods with two, three and four-ports have been frequently used as VATS applications. In recent years, single-port VATS procedure has become commonly used [1][2][3][4] . In this study, the results of 16 patients with spontaneous pneumothorax who were treated by single-port VATS in our clinic have been reported.…”
Section: Introductionmentioning
confidence: 99%